PELATIHAN DIGITAL MARKETING BAGI PARA PELAKU UMKM - Arief Budiman; Candra Budi Susila; Laily Fatmawati (Universitas Merdeka Madiun, 2025)
Social media is a form of marketing system that combines electronic media with users. Facebook is a social media platform that is widely used for sales purposes and various other information. Many UMKMs sell anchovy and peanut crackers. It is hoped that UMKM owners can increase their product sales, one of which is by conducting socialization using Facebook social media, with benchmarks used to expand sales reach and the expected level of stability. The socialization method is used for UMKM owners to promote their products more deeply. The results of this study indicate that Facebook increases sales through increased use by the community and use by the community. Because Facebook has made it easier to market UMKM products, this study found that UKM owners have used Facebook to sell their goods. Because Facebook itself can prevent interaction between sellers and buyers, which allows for the distribution of products that are right and easily accessible to customers, Facebook users themselves will help market the goods sold